KERAGAMAN GENETIK PANDAN ASAL JAWA BARAT BERDASARKAN PENANDA INTER SIMPLE SEQUENCE REPEAT (Makara Journal of Science, 2010)
Genetic Diversity of Pandanus from West Java based on ISSR Markers. The genetic diversity of 10 species of Pandanus from West Java was examined using inter simple sequence repeat (ISSR) technique. Samples were collected from different localities in West Java. Two primers (ISSR2 and ISSR7) were selected as reliable amplifying ISSR markers. The two primers amplified 19 band position, with amplification size ranged from 200 to 1500 bp. Genetic distance for samples ranged from 0.267 to 0.957. Genetic distance was high (0.957) between P. pseudolais and P. spinistigmaticus, and between P. kurzii and P. pseudolais, where as genetic distance was low (0.267) between P. scabrifolius and P. bidur.